2020
DOI: 10.1371/journal.pone.0237159
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and cost estimation of laboratory test overuse in 43 commonly ordered parameters through a Computerized Clinical Decision Support System (CCDSS) in a large university hospital

Abstract: Background Computerized Clinical Decision Support Systems (CCDSS) have become increasingly important in ensuring patient safety and supporting all phases of clinical decision making. The aim of this study is to evaluate, through a CCDSS, the rate of the laboratory tests overuse and to estimate the cost of the inappropriate requests in a large university hospital. Method In this observational study, hospital physicians submitted the examination requests for the inpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The behaviour of not seeking treatment for urgent care conditions needs to be addressed in preparation for further possible COVID‐19 restrictions and other pandemics. Conversely, overuse of pathology testing is a known issue in healthcare services and leads to increased risk of harm to patients and contributes to overspending in the health system 16 . A systematic review of published studies on inappropriate pathology testing found an overall rate of overutilisation of testing of more than 20% 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The behaviour of not seeking treatment for urgent care conditions needs to be addressed in preparation for further possible COVID‐19 restrictions and other pandemics. Conversely, overuse of pathology testing is a known issue in healthcare services and leads to increased risk of harm to patients and contributes to overspending in the health system 16 . A systematic review of published studies on inappropriate pathology testing found an overall rate of overutilisation of testing of more than 20% 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Change ideas to limit blood requests have focused on improving knowledge, changing systems, and financial implications. [2][3][4]6,13 Wertheim et al demonstrated a reduction in blood ordering in an adult general medical service. 2 Similar to our project, change ideas included education and the development of written guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…1–3 Tamburrano et al identified a consistent rise in blood tests by approximately 5% per annum over the past ten years in the United States and Europe. 4 Indeed, health economists estimate that a fifth of spending in healthcare is ineffective and even wasteful. 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonadherence to guidelines may be due to ignorance regarding cost of the tests, uncertain diagnosis, defensive medicine practice, and the wide range of available tests. 26 These practices lead to increased hospital costs, hospital-acquired anemia, and unnecessary additional laboratory and radiological tests. 27…”
Section: Evaluation Of Patients With Hemorrhagic Riskmentioning
confidence: 99%